Thermal Instability of a Rivlin-Ericksen Nanofluid Saturated by a Darcy-Brinkman Porous Medium: a More Realistic Model - G. C. RANA; Ramesh CHAND; Veena SHARMA (Engineering Transactions, 2016)
In this paper, we study thermal instability in a horizontal layer of Rivlin-Ericksen elastico-viscous nanofluid in porous medium. Brinkman model is used as a porous medium and Rivlin-Ericksen fluid model is used to describe the rheological behavior of nanofluid. In the earlier model (Chand and Rana [18]), we constrained both temperature and nanoparticle volume fractions at the boundaries of Rivlin-Ericksen nanofluid layer. In this paper, we assume that the value of temperature can be constrained on the boundaries, while the nanoparticle flux is zero on the boundaries. The considered boundary condition neutralizes the possibility of oscillatory convection due to the absence of two opposing forces, and only stationary convection occurs, in which Rivlin-Ericksen elastico-viscous nanofluid behaves like an ordinary nanofluid. The effects of Lewis number, medium porosity, modified diffusivity ratio, Darcy-Brinkman number and concentration Rayleigh number in stationary convection are discussed analytically and numerically. The results of this study are in good agreement with the results published earlier [11–21].